Lura system of the Galos: A study of its origin and socio-religious significance - Doge Nyori; Reken Lollen (Dera Natung Government College Research Journal)
Mithun, also popularly known as ‘Cattle of Mountain’ is an important bovine species of north-eastern region of India and also of China, Myanmar, Bhutan and Bangladesh. Mithuns are presently reared under free-range condition in the hill forests. Mithun plays an important role in the socio-economic and cultural life of the Galo people. However, with the dwindling population of Mithun over the years and gradual denudation of free-range area along with the biotic and abiotic stress, there is urgent need of scientific intervention and practicing the aged old traditional method of Mithun management (Lura) for proper management as well as conservation of this beautiful hill animal. This article is an attempt to highlight the significance and various important facets associated with the Lura system of the Galos of Arunachal Pradesh.